Molecular Modelling Based on TD-DFT Applied to UV Spectra of Coumarin Derivatives - Ariefin, Mokhamat; Alfanaar, Rokiy (Walisongo Journal of Chemistry, 2023)
The optimization of geometry and electronic transition of seven coumarin derivatives for sunscreen activity have been conducted using Orca. DFT methods is applied to find optimum geometry and parameter data is measured like bond length and bond angle. TD-DFT is conducted to get electronic transition to get ultraviolet (UV) spectra. The result shows that the coumarin derivative transition type is n to π* and π to π*. All coumarin exhibits the properties of UV-B protection, however, two out of seven show properties as a UV-A protection. The energy difference HOMO-LUMO shows that coumarin with isopropyl substituent has the smallest energy gap, around 0.1559, whereas coumarin with fluorine atom substituent has the biggest energy gap.